(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Background Advancement in the understanding of the anatomy of distal femur and fracture healing biology have led to the development of various implant designs optimizing the successful treatment of these injuries. Proper fit and positioning of the implant are mandatory to avoid complicationssuch as intra-articular screw penetration, PCL impingement, etc. DF-LCP [Distal femur - Locking compression plate], an anatomical plate used currently has been developed based on skeletal measurements from the western world. This study aims to determine the optimal position of LCP with the anatomical landmarks, identify problem screws and recognize the use of intraoperative notch view to assessing screw placement. This has not been attempted before as evidenced by the available literature. Materials and methods 48 adult femurs harvested from cadavers were grouped based on the length and side [group A – 42 +/-3cm & group B – 36 +/-3cm]. DF-LCP from 3 different manufacturers were fixed in 4 different positions [S3, I3, 0, A3] with respect to the lateral epicondyle and the long axis of the distal femur. Clinical and radiographic assessment were done to assess the positions of the plate with intra-articular screw penetration. Results The total incidence of screw penetration with inferior and postero-inferior locking screws of the distal end of plate was found to be 54.16 %. Irrespective of implant and side variation, superior position (S3) had better results with zero screw penetration. 100% screw penetration was encountered in the inferior position(I3). Conclusion: The positioning of the central hole of DF-LCP 3mm proximal to lateral epicondyle along the long axis of distal femur or avoidance of inferior and posterior screw holes of LCP can prevent intra-articular screw penetration. An intraoperative notch view to recognize screw placement can be done. Designing a plate without compromising stability for the Indian population will be more effective.